2019
DOI: 10.1177/2165079919844273
|View full text |Cite
|
Sign up to set email alerts
|

The Nurse With a Profound Disability: A Case Study

Abstract: Nurses are at significant risk for work-related injury, and ultimately disability. The purpose of this intrinsic single-case study guided by Yin’s and Stake’s iterative analytic processes was to examine one case of a registered nurse with a profound disability to determine whether this experience aligned with previous research and to examine whether a nurse with a profound physical disability could remain working in a clinical setting. The case study subject (a nurse with a profound physical disability) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In two studies, patient safety concerns were expressed by colleagues and patients. One concern was the ability of the nurse or midwife with a disability to respond to emergencies, particularly if the disability was considered profound and a colleague was required to pick up clinical tasks not met by the nurse or midwife with disabilities (Neal-Boylan, 2019). Additionally, colleagues were concerned the quality of care provided would be compromised when limitations of a disability impacted the ability to perform procedures or tasks (Lövgren et al, 2014).…”
Section: Patient Safety Concernsmentioning
confidence: 99%
“…In two studies, patient safety concerns were expressed by colleagues and patients. One concern was the ability of the nurse or midwife with a disability to respond to emergencies, particularly if the disability was considered profound and a colleague was required to pick up clinical tasks not met by the nurse or midwife with disabilities (Neal-Boylan, 2019). Additionally, colleagues were concerned the quality of care provided would be compromised when limitations of a disability impacted the ability to perform procedures or tasks (Lövgren et al, 2014).…”
Section: Patient Safety Concernsmentioning
confidence: 99%
“…Previous research studies (Aaberg, 2012;Ailey et al, 2016;Kritsotakis et al, 2017;Luckowski, 2016;Neal-Boylan & Guillett, 2008a;2008b;Neal-Boylan, Fennie & Baldauf-Wagner, 2011;Neal-Boylan, 2012;Neal-Boylan et al, 2012) revealed that nurses were unaware of the requirements of the ADA or how they might be violating them by discriminating against nurses with disabilities. The studies that followed (Davidson et al, 2016;Neal-Boylan & Miller, 2015;Neal-Boylan & Miller, 2017;Neal-Boylan, Miller & Bell, 2018;Neal-Boylan, 2019;Shpigelman & Zlotnick, 2016) focused on increasing that awareness. Nurses who had disabilities while in nursing school and were employed as nurses shared that they wanted to be treated like everyone else (Neal-Boylan & Miller, 2017).…”
Section: Students With Disabilitiesmentioning
confidence: 99%
“…Studies have shown that faculty misconceptions regarding what students with disabilities can do safely is the primary barrier to admitting and retaining these students (Carey, 2012;Davidson et al, 2016;Neal-Boylan & Miller, 2018, Neal-Boylan & Miller, 2017. Similarly, the lack of supportive administrators is the primary barrier to the employment of nurses with physical disabilities in clinical settings (Neal-Boylan, 2014;Neal-Boylan & Guillett, 2008b;Neal-Boylan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses, administrators, and colleagues may view nurses with disabilities as unsafe in the workplace. Not only is there no evidence to support that perception but nurses with disabilities may be better nurses because they know what it is like to be a patient, and they live every day with the struggles and compensations inherent in having a disability (Neal-Boylan, 2019). Nurses with disabilities experience discrimination in the workplace (Matt, 2008; Neal-Boylan, 2012).…”
mentioning
confidence: 99%
“…Yet, these nurses are in the best position to empathize with patients. Having a disability or a disabling chronic illness frequently requires that person to plan their day carefully, predetermine what they will need to do differently to ensure they provide safe care, and figure out how best to utilize and conserve their energies and prioritize physically or mentally taxing tasks (Neal-Boylan, 2019). Nurses with disabilities compensate by sometimes doing things in nontraditional ways.…”
mentioning
confidence: 99%